Determination of Isosorbide-5-Mononitrate in Human Plasma by High-Performance Liquid Chromatography-Tandem Mass Spectrometry and Its Application to a Bioequivalence Study. (17th July 2020) - Zhou, Yinping; Liu, Aijing; Jia, Ranran; Wu, Mengyi; Wu, Ni; Liu, Chunyan; Han, Zhihui; Hu, Haitang; Wang, Hongyun; He, Qing
Abstract : Isosorbide-5-mononitrate (5-ISMN), an organic nitrate vasodilator, has been widely used worldwide to prevent angina pectoris for more than two decades. A simple and sensitive high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method was developed and validated for the determination of 5-ISMN in human plasma. 13 C6 -5-ISMN is an internal standard, and 5-ISMN was extracted from human plasma (50  µ L) with ethyl acetate (200  µ L) by a simple liquid-liquid extraction method. The chromatographic separation was carried out on LC-20A (Shimadzu, Japan) using an analytical column ZORBAX XDB-C18 (4.6 × 50 mm, 5  µ m), coupled with API 4000 tandem mass spectrometers in a multiple reaction monitoring (MRM) mode. The mobile phase was composed of acetonitrile (organic phase A) and 2 mM ammonium acetate in water (aqueous phase B) with an isocratic elution of A/B = 90 : 10 (v / v ). The total run time was 3.5 min with a small injection volume (5  µ L). This method was fully validated in every aspect of selectivity, linearity, accuracy, precision, matrix effect, extraction recovery, and different stabilities. It was proved that the calibration standards within the 5.00–1000 ng/mL concentration range were linear. The lower limit of quantification was 5.00 ng/mL for 5-ISMN. The intrabatch and interbatch accuracy (RE) ranged from −8.8% to 7.1% with precision between 2.4% and 6.6%. The mean values of 5-ISMN extraction recovery and matrix effect were 87.0% and 102.0%, respectively. The fully validated method was successfully applied for a bioequivalence clinical trial of oral 20 mg 5-ISMN tablets in healthy Chinese subjects.